Mycosis Fungoides Involving the Dorsal Tongue - Ashley E. Brown; Lindsey Schmidtberger; Kathleeen Kroger; Richard R. Jahan-Tigh; Sarah S. Pinney (Case Reports in Dermatological Medicine)
Mycosis fungoides (MF) is a rare cutaneous T-cell lymphoma (CTCL) which can cause significant morbidity. ​During​ ​the​ ​disease course, ​​ ​it​ ​classically​​ ​will​ ​progress​ ​through​ ​three​ ​clinical​ ​stages​ ​in​ ​the​ ​skin​: ​ ​patch-,​ ​plaque-,​ ​and tumor-stage.​ The early stages exhibit​ ​various​ ​histopathological​ ​mimics​ ​that​ ​often​ ​lead​ ​to misdiagnosis.​ It rarely affects the oral cavity. Oral MF is historically associated with poor prognosis. We present a rare case of MF afflicting the dorsal tongue and extremities of a 72-year-old male.